RETRACTED: E-leadership Practices and Implication for Higher Educations: A Systematic Review Protocol - Dibaba, Demie Bedada; Tefera, Bekalu Ferede; Debelo, Desalegn Beyene (International Journal of Humanities, Education, and Social Sciences, 2024)
E-leadership practices in developed countries are employed for leadership in business and industry which is an applicable system that is advantageous for leaders and employers to connect simply through technology. However, e-leadership practices in higher education, specifically in developing countries, need further investigation. To gain insight into this gap in e-leadership practices in higher education, this systematic review will search and analyze e-leadership practices from developed to developing countries in different disciplines with different methodologies which have implications for higher education. For this systematic review, the databases GOOGLE SCHOLAR, PUBMED and IEEE XPLORE will be utilized. Articles published in the English language that focus on e-leadership practices in different disciplines will be eligible. The evidence will be searched and data will be extracted on the similarities and differences between e-leadership practices in previous research. Indicating the searched evidence in methodology, geography, and discipline will determine how many e-leadership practices exist. I will ensure that all articles are checked and address e-leadership practices in different disciplines and contexts to provide vital ideas and implications for higher educations.